Exploring the Italian Space of Lifestyles: Food, Class, and Their Homology - Bilevicius, Tomas (Italian Sociological Review, 2024)
In his prominent Distinction, Bourdieu captured a homology between spaces of lifestyles and social positionings in 1960s France, in which he discerned a relationship between tastes of necessity and tastes of luxury, regarding numerous culturally-defined consumables, food included. Ever since, the relation between social actors’ positionings, food consumption, and tastes has been explored in other European countries, but not yet in Italy. Against this background, from cultural-sociological and post-structuralist points of view, this study argues that to comprehend how food, invested with cultural and moral meanings, is being used to differentiate, it is necessary to map the homology between tastes and positions. It explores this relationship by using quantitative data from the Italian household budget survey, focusing on the expenditure on food. The study finds that regardless of previously recorded regional variations in foodways and cuisines, tastes of necessity and luxury can be identified. In the case of the former, consumed foods are predominantly associated with function, substantiality, cheapness, heaviness, and tradition, while in the case of the latter, it distances itself from necessity through foods that are exclusive, lighter, more expensive, fiddly to eat, exotic, and are consumed in all due form. Positioned relationally, such distinction through taste points towards a mechanism whereby ingesting said foods, social actors likewise embody the associated moral properties and participate in a constant struggle of worth. The article concludes with recommendations for the necessary further explorations of spaces of positionings and lifestyles in Italy.